Hammering with the telescope - Sobkowicz, Pawel (Frontiers in Artificial Intelligence, 2022)
The rapid pace at which various Artificial Intelligence and Machine Learning tools are developed, both within the research community and outside of it, often discourages the involved researchers from taking time to consider potential consequences and applications of the technical advances, especially the unintended ones. While there are notable exceptions to this ``gold rush" tendency, individuals and groups providing careful analyses and recommendations for future actions, their adoption remains, at best, limited. This essay presents an analysis of the ethical (and not only) challenges connected with the applications of AI/ML methods in the socio-legal domain.